Patient perspectives: Four pillars of professionalism - Laura Bulk (The Beryl Institute, 2019)
Professionalism is a core component of healthcare practice and education; however, there is often not a consistent description of professionalism, and current definitions lack a key perspective: that of the patient. This study aimed to deepen understandings of patients’ perspectives on how professionalism should be enacted by healthcare providers. Using a phenomenological approach informed by constructivist theory, the study team conducted semi-structured interviews and focus groups with 21 patients to ascertain their views on professionalism. Data analysis was conducted using a constant comparative approach wherein initial analysis informed subsequent data collection. Participant themes fell into four pillars of professionalism: taking a collaborative human-first approach; communicating with heart and mind; behaving with integrity; and practicing competently. This study highlights patient perspectives on professionalism and examines consistencies and differences between those perspectives and those of healthcare providers, which are extensively described in the literature. While published literature highlights competence and communication as main aspects of professionalism which our participants also focused on, participants in this study emphasized integrating patients into care teams, employing empathy, and demonstrating integrity. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.